Development of Shipping Sector in Pakistan: Options and Proposed Strategy - Sajid Mehmood Shahzad; Umbreen Javaid (Journal of Political Studies, 2016)
With the dawn of the modern era the leading nations of the world have realized that with increasingly shrinking rate of land resources focus needs to be laid towards exploiting maritime resources as an equal alternative. In this regard the developed modern nations of the world have built considerable infrastructure to fully accrue the benefits which lay in the uncharted marine sector. The geographical location of Pakistan is such that it intersects the sea lines of communication (SLOCs) immerging from the three main choke points in the Indian Ocean i.e. Strait of Melaka, Strait of Hormuz and Red Sea. Pakistan can take advantage of its location by developing maritime infrastructure all along its coast. Owing to land fixated mindset, Pakistan is already late in realising the true potential of its huge maritime sector and the progress in this field has been deemed slow. However after the manifestation of China Pakistan Economic Corridor (CPEC) with a cost of US$ 46 Billion contract linking Gwadar port with western China there is a realization of developing the maritime sector of Pakistan. Although Karachi shipyard is on the road to recovery and has started making profit with recently received orders from Pakistan Navy, Karachi Port Trust and Pakistan Maritime Security Agency for Ship Construction, still there is a need for viable economic reforms. It appears that the Pakistan Ship breaking Industry is in shambles working without safety and health security. The recent incident of accidental fire on 1st Nov 2016 at Gadani dictates that entire industry needs to be restructured on modern lines. The current state of affairs of Pakistan National Shipping Corporation can be judged by the fact that a fleet of only nine ships is being maintained which presently only lifts five percent of the national cargo. Keeping in view the depleting state of maritime relating organizations it is recommended that Pakistan Merchant Marine Policy be revised to meet the challenges of the prevailing scenario.